Integrating Crop Rotation and Critical Periods of Weed Control to Enhance Ecological Resilience and Yield Stability: A Review: Integrasi Rotasi Tanaman Dan Periode Kritis Pengendalian Gulma Guna Meningkatkan Resiliensi Ekologis Dan Stabilitas Hasil - Bela Tri Wijayanti; Qaanitatul Hakim Ipaulle; Aulia Adillah (Gontor Agrotech Science Journal, 2025)
Meeting global food demands amidst climate volatility and resource scarcity has historically driven agricultural intensification. However, this pursuit of maximized yields through continuous monoculture and high agrochemical inputs has precipitated severe ecological costs, including biodiversity erosion, soil degradation, and heightened vulnerability to biotic stressors. While Sustainable Land Management (SLM) offers a restorative framework, its core principle of minimal soil disturbance often exacerbates weed pressure, creating a trade-off between ecological preservation and crop productivity. This extensive review consolidates systematic literature from 2000 to 2024 to critically assess the combined impact of Crop Rotation and the Critical Period of Weed Control (CPWC) in effectively addressing this agronomic challenge. The analysis demonstrates that crop rotation serves as the ecological foundation, restoring soil multifunctionality, restructuring microbial networks, and disrupting pest cycles. Complementing this, the CPWC functions as a vital tactical tool for precision management, allowing farmers to restrict weed interventions to specific phenological windows. This integration minimizes soil disturbance and chemical reliance without compromising harvest outcomes. According to the review, combining the natural benefits of crop rotation and the efficiency of CPWC is an effective strategy for intensification. This method ensures that farming remains productive without damaging the ecosystem.